Experimental study on shear behavior of Polyurethane/water glass-filled planar rock joints. - Hao Yu; Richeng Liu; Dedong Xiao; Shuchen Li; Xiaochuan Han; Minghui Hu; Yiyang Wang (PLoS ONE)
Rock joints are widespread in nature and have become a major obstacle to the safe development of underground space. Grouting reinforcement is widely adopted to reduce engineering disasters induced by joint sliding instability. In this study, direct shear tests of Polyurethane/water glass (PU/WG)-filled planar rock joints under constant normal stress conditions were carried out to investigate the effects of normal stress σn, PU/WG layer and curing time T on the shear behavior, shear strength and surface damage of filled joints. The results show that PU/WG significantly enhances the peak shear strength of rock joints by 270.9% compared to the unfilled planar joints at σn = 2 MPa. However, the increase in σn reduces the improvement of shear strength for PU/WG-filled joint. With the increase of curing time, the shear strength increased rapidly within the first 10 minutes, reaching 0.2-0.31 MPa/min. After the curing time exceeds 60 min, the shear strength enhancement declines significantly. Two typical shear displacement ds and shear stress τs curves are proposed, related to σn and filled layer. At low normal stress, such as σn = 2 MPa, the τs decreases sharply after reaching the peak shear stress for the fracture of PU/WG-rock interface. However, under high normal stress conditions, an obvious post-peak yield stage is observed, and the τs in the residual stage fluctuates within a certain range. High normal stress and PU/WG layer are the two necessary conditions for stick-slip in the residual stage. After shearing, the PU/WG remains largely intact on the upper surface, with few residual layers at the boundary on the lower surface. The PU/WG layer is relatively complete, with local tensile cracks, primarily V-shaped, and a few linear cracks. These findings provide valuable insights into the mechanical behavior and reinforcement effect of PU/WG filled in fractured surrounding rocks.